ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN KLINIK GIGI SVARTA DENTAL CARE BANDUNG - Refliza Yanti; Dety Mulyanti (Lembaga Pengembangan Kinerja Dosen, 2023)
The quality of health services is closely related to satisfaction. This study aims to determine the level of satisfaction and analysis (expectation and reality) of the quality of dental health services at the Svarta Dental Care Bandung clinic. This research is a descriptive research. The research sample is 30 people. sampling method with accidental sampling. The research was conducted from January 3 to January 18, 2023. The research instrument used a questionnaire. The data analysis used is univariate analysis and Importance Performance Analysis (IPA), namely by using a Cartesian diagram. The results showed that the level of conformity between reality and expectations was based on the five dimensions of quality in the Reliability dimension of 87.3%, the Responsiveness dimension of 85.75%, the Assurance dimension of 90.06%, the Empathy dimension. 90.18% work tidiness (tiness) 90.94%. Based on the results of the study, it is recommended to carry out regular evaluations every 6 months, repairs by providing training and collaboration with officers in improving the quality of service that focuses on patient satisfaction.